2006
DOI: 10.1002/bit.21076
|View full text |Cite
|
Sign up to set email alerts
|

Surface display of transglucosidase onEscherichia coli by using the ice nucleation protein ofXanthomonas campestris and its application in glucosylation of hydroquinone

Abstract: A surface anchoring motif using the ice nucleation protein (INP) of Xanthomonas campestris pv. campestris BCRC 12,846 for display of transglucosidase has been developed. The transglucosidase gene from Xanthomonas campestris pv. campestris BCRC 12,608 was fused to the truncated ina gene. This truncated INP consisting of N- and C-terminal domains (INPNC) was able to direct the expressed transglucosidase fusion protein to the cell surface of E. coli with apparent high enzymatic activity. The localization of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…In our previous work on the construction of recombinant E. coli displaying transglucosidase, we focused on the enzymatic characteristics of the whole cells in hydroquinone glucosylation [26]. We wish to extend this work to establish a high cell density culture for the production of E. coli cells displaying transglucosidase for use as biocatalysts, for large-scale production of -arbutin by glucosylation of hydroquinone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work on the construction of recombinant E. coli displaying transglucosidase, we focused on the enzymatic characteristics of the whole cells in hydroquinone glucosylation [26]. We wish to extend this work to establish a high cell density culture for the production of E. coli cells displaying transglucosidase for use as biocatalysts, for large-scale production of -arbutin by glucosylation of hydroquinone.…”
Section: Discussionmentioning
confidence: 99%
“…Sam7 nin5 lacUV5-T7 gene 1)] was transformed with plasmid pInaXNC1-aglA for the expression of INPNC-transglucosidase fusion protein [26]. The growing E. coli cells were induced with IPTG or lactose to express the fusion protein.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By fusing various target proteins to the C-terminus of INP, it was found that the engineered host cell had the surface-localized activities of the target proteins [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%